Respuesta :

Answer:

C.   [tex] f(a + 2) = \dfrac{5 + a}{a - 1} [/tex]

Step-by-step explanation:

Replace x with a + 2 and simplify the expression.

[tex] f(x) = \dfrac{3 + x}{x - 3} [/tex]

Let x = a + 2

[tex] f(a + 2) = \dfrac{3 + a + 2}{a + 2 - 3} [/tex]

[tex] f(a + 2) = \dfrac{5 + a}{a - 1} [/tex]

For this case we have a function of the form [tex]y = f (x).[/tex] Where:

[tex]f (x)=\frac {3 + x}{x-3}[/tex]

We must find the value of the function when [tex]x = a + 2[/tex]

So, substituting the value of "x" we have:

[tex]f (a + 2) = \frac {3+ (a + 2)} {(a + 2) -3}[/tex]

[tex]f (a + 2) = \frac {3 + a + 2} {a + 2-3}[/tex]

[tex]f (a + 2)=\frac {5 + a} {a-1}\\[/tex]

Answer:

[tex]f(a + 2) =\frac {5 + a} {a-1}[/tex]

Option C